2017
DOI: 10.1371/journal.pone.0174177
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 in blood mononuclear cells from patients with coronary artery disease: Its association with inflammatory status and glucocorticoid sensitivity

Abstract: Annexin A1 (AnxA1) is a key player in resolution of inflammation and a mediator of glucocorticoid actions. In atherosclerotic tissue, increased expression of AnxA1 has been associated with protective plaque-stabilizing effects. Here, we investigated the expression of AnxA1 in peripheral blood mononuclear cells (PBMCs) from patients with coronary artery disease (CAD). Blood was collected from 57 patients with stable CAD (SCAD) and 41 healthy controls. We also included a minor group (n = 10) with acute coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…The association between estrogens and ANXA1 has been previously documented in vitro, and it is well established that hormonal changes influence the composition of saliva, including changes in the protein profiles or the levels of ROS in pregnant women . It may also be stated that ANXA1 is increased in the plasma of women with preeclampsia, and that periodontitis is also associated with preeclampsia and reversed pregnancy outcomes . Collectively, these earlier studies are supported by the present findings demonstrating that ANXA1 levels are increased in the course of gingival inflammation during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…The association between estrogens and ANXA1 has been previously documented in vitro, and it is well established that hormonal changes influence the composition of saliva, including changes in the protein profiles or the levels of ROS in pregnant women . It may also be stated that ANXA1 is increased in the plasma of women with preeclampsia, and that periodontitis is also associated with preeclampsia and reversed pregnancy outcomes . Collectively, these earlier studies are supported by the present findings demonstrating that ANXA1 levels are increased in the course of gingival inflammation during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study exhibited that there was an increased AnxA1 expression in patients with ACS in response to glucocorticoid mediated acute inflammation. (17) In contrast to our study, a study on patients with CHD to evaluate the expression of AnxA1, showed that despite the anti-inflammatory effect of statins there was no change in the expression of glucocorticoids or AnxA1 (18) .…”
Section: Discussioncontrasting
confidence: 99%
“…The observed protective effects of Ac2-50 (a synthetic peptide of the last 28 amino acid of the N-terminal fragment of ANXA1) were lost in FRP2/3 −/− mice suggesting that activation by Ac2-50 of the ALX/FPR2 confers tissue protection (54). In patients with stable coronary artery disease, Bergström et al describe that ANXA1 located on the surface of peripheral monocytes serves as a marker of glucocorticoid sensitivity, thereby reflecting the anti-inflammatory capacity of these cells (55).…”
Section: Anxa1: An Anti-inflammatory Mediatormentioning
confidence: 99%